Determinan Dari Niat Investasi Saham Syariah: Perspektif Toleransi Maghrib - Ustman Ustman; Subhan Subhan; Rohmaniyah Rohmaniyah (Jurnal Akademi Akuntansi, 2022)
Islamic finance is a sharia-compliant business sector. The factor of religion or sharia compliance is very important to encourage the intention of Muslims to use Islamic financial products. The failure of Islamic financial products to comply with sharia principles has become a major barrier for investors. This leads to the purpose of this paper to reveal the determinants of investment intentions in Islamic stocks with the perspective of MAGHRIB tolerance regulated by the OJK. Sample data from 200 respondents were collected from students of the Economics and Business Faculty at Wiraraja University, Madura University, and Trunojoyo University using purposive sampling method and the data were analyzed using multiple linear regression techniques. The Theory of Planned Behavior is used as the basic framework in which the MAGHRIB tolerance becomes a consensus to test attitudes, subjective norms, and perceived behavioral control on Islamic stock investment intentions. The results showed that MAGHRIB tolerance had a significant relationship consisting of attitudes, subjective norms, perceived behavioral control on Islamic stock investment intentions. The findings of this study can be useful for increasing investment in Indonesia, especially for students to start investing in Islamic stocks.